Optimlisasi Kemampuan Interaksi Sosial Anak di PAUD Inklusi Ahsanu Amala Yogyakarta - Nadlifah, Nadlifah (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2016)
Education is a social process that can't happen without interaction between individuals Learning is a personal and social proccess when the child is in touch with other children in building understanding and knowledge together. Generally, Early Childhood have a low social interactions skill. This is evidenced by the frequent fights with his friend and selfish. Similarly in general, children who have mental disorders such as children with autism, Down syndrome, the hearing impaired etc, has the low skill ability in social interaction and communication. children who have maximum social interaction skills will be easier to be accepted in the school environment, especially in a classroom environment. Therefore it the children of inclusion is still an early age need to be assisted in improving the ability of social interactions at school, because the period of early childhood is a period of development the right to develop, improve and optimize all the capabilities of a child, even this period is an effective time to train and familiarize children to develop social interaction skills of children.